Evaluating Greenhouse Gas Emissions and Climate Mitigation Goals of the Global Food and Beverage Sector - Reavis, Megan; Ahlen, Jenny; Rudek, Joe; Naithani, Kusum (Frontiers in Sustainable Food Systems, 2022)
The dramatic increase of emitted greenhouse gases (GHGs) by humans over the past century and a half has created an urgency for monitoring, reporting, and verifying GHG emissions as a first step towards mitigating the effects of climate change. Fifteen percent of global GHG emissions come from agriculture, and companies in the food and beverage industry are starting to set climate goals. We examined the GHG emissions reporting practices and climate goals of the top 100 global food and beverage companies and determined whether their goals are aligned with the science of keeping climate warming well below a 2 °C increase. Using publicly disclosed data in CDP Climate reports and company sustainability reports, we found that over two thirds of the top 100 (as ranked by Food Engineering) global food and beverage companies disclose at least part of their total company emissions and set some sort of climate goal that includes scope 1 and 2 emissions. However, only about half have measured, disclosed, and set targets for scope 3 emissions, which often encompass more than 87% of a company’s emissions across the entire value chain. We also determined that companies, despite setting scope 1, 2, and 3 targets, may be missing the mark on whether their targets are significantly reducing global emissions. Our results present the current disclosure and emission goals of the largest food and beverage companies and highlight an urgent need to begin and continue to set truly ambitious, science-aligned climate goals.